Automatización de procesos académicos en la sección de tecnologías del Instituto Tecnológico Superior "Daniel Álvarez Burneo". - Lara Tapia, Soraya Isamar (2017)
This current degree work is focused on the development of the system - Automation of Academic Processes at the technology section of the Instituto Tecnológico Superior "Daniel Álvarez Burneo"-, which provides its services to the community through the formation of professionals in several areas at the technical-technologies level. The system is based on a responsive web environment that adapts to the device which is displayed, so that the user can perform various processes such as: edit, enter, delete, unsubscribe, restore, generate reports, and view information concerning assists, ratings, academic curriculum, cycles, scholarships, financial aid, registration and specialties. The system is based on a responsive web environment which adapts to the device which is being displayed, the user can perform different processes such as: edit, enter, delete, drop, restore, generating reports and see the information about to attendance, grades, curriculum, courses, scholarships, financial aid, tuition and specialties. The functionality of the system was achieved by applying the methodology Iconix, whose phases include: determination of the user's requirements (allows you to meet the needs of the same), preliminary design and detailed system (defined diagrams of robustness and sequence which establish the iterations that are the objects of the system), implementation of the system (encoding using the programming language PHP with the Codeigniter framework and tools for the design like Boostrap and MySql database), and finally, verifies the correct operation of the system with the application of unit tests (performed with the UnitTest library, validation with Jquery, usability through tabulation of surveys and loaded through Apache Jmeter). The information collected in the development of each of the phases of the Iconix methodology is documented (surveys, interviews, observation and approval of prototyping) and served as the basis for the formulation of conclusions and recommendations.